OPTIMALISASI SUPERVISI MANAJEMEN KEPERAWATAN DALAM MENDUKUNG KINERJA TIM KEPERAWATAN - Metilda; Zahwa Salsabila; Mirna Laras Santi; Silvi Rahmawati; Farid Rasyid Faqih; Kurnia Ramdani (Lembaga Pendidikan dan Penelitian Manggala Institute, 2026)
Nursing management supervision is one of the managerial functions that plays an important role in improving the performance of the nursing team. The optimal implementation of supervision focuses not only on supervision, but also includes coaching, mentoring, and ongoing evaluation of nurses. This article aims to examine the role of nursing management supervision optimization in supporting the performance of nursing teams. The writing method used is a literature study by examining various scientific sources in the form of nursing textbooks and relevant journal articles in the last ten years. The results of the study show that nursing management supervision carried out in a planned, systematic, and continuous manner is able to improve the performance of the nursing team, which is characterized by increased compliance with nursing care standards, documentation quality, team communication, and nurse job satisfaction. In addition, supportive and educational supervision can increase the motivation and responsibility of nurses in providing quality nursing care. Therefore, the optimization of nursing management supervision needs to be applied consistently by nursing leaders as an important strategy in improving the performance of the nursing team and the quality of health services.